Chronic Inflammation and γδ T Cells - Fay, Nathan S.; Larson, Emily C.; Jameson, Julie M. (Frontiers in Immunology, 2016)
The epithelial tissues of the skin, lungs, reproductive tract, and intestines are the largest physical barriers the body has to protect against infection. Epithelial tissues are woven with a matrix of immune cells programmed to mobilize the host innate and adaptive immune responses. Included among these immune cells are  T cells that are unique in their TCR usage, location, and functions in the body. Stress reception by  T cells as a result of traumatic epithelial injury, malignancy, and/or infection induces  T cell activation. Once activated,  T cells function to repair tissue, induce inflammation, recruit leukocytes, and lyse cells. Many of these functions are mediated via the production of cytokines and growth factors upon  T cell activation. Pathogenesis of many chronic inflammatory diseases involve  T cells; some of which are exacerbated by their presence, while others are improved.  T cells require a delicate balance between their need for acute inflammatory mediators to function normally and the detrimental impact imparted by chronic inflammation. This review will focus on the recent progress made in understanding how epithelial  T cells influence the pathogenesis of chronic inflammatory diseases and how a balance between acute and chronic inflammation impacts  T cell function. Future studies will be important to understand how this balance is achieved.